Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.